1998
DOI: 10.1021/es980232m
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pyromorphite in Anglesite-Hydroxyapatite Suspensions under Varying pH Conditions

Abstract: Addition of phosphate to lead [Pb(ll) Pb from anglesite to'chloropyromorphite. Increasing the P/Pb ratio increased the transformation rate, but anglesite was still present after a' 120-min reaction time. in the dynamic pH system, the added apatite was rapidly dissolved at the initial low pH, and complete transformation of anglesite to chloropyromorphite was obtained within 25 min., The soluble Pb level was controlled by the solubility of chloropyromorphite during the entire reaction process. These results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 21 publications
5
74
1
1
Order By: Relevance
“…The dialysis systems used in this study were designed to study the dissolution of phosphate and solid-phase Pb, dissociation of Pb, and formation of Pb-P compounds (20). Although it has been demonstrated that hydroxyapatite is able to provide sufficient phosphate to immobilize Pb in solutions as pyromorphite (9,13), Pb adsorbed on goethite (20), and Pb primary minerals (21)(22)(23), this process has not been demonstrated in a -complex soil system. In addition, the dialysis system used in this study helps isolate the reaction product(s) for a direct observation with proper instruments as illustrated in related studies in our laboratory (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dialysis systems used in this study were designed to study the dissolution of phosphate and solid-phase Pb, dissociation of Pb, and formation of Pb-P compounds (20). Although it has been demonstrated that hydroxyapatite is able to provide sufficient phosphate to immobilize Pb in solutions as pyromorphite (9,13), Pb adsorbed on goethite (20), and Pb primary minerals (21)(22)(23), this process has not been demonstrated in a -complex soil system. In addition, the dialysis system used in this study helps isolate the reaction product(s) for a direct observation with proper instruments as illustrated in related studies in our laboratory (20).…”
Section: Resultsmentioning
confidence: 99%
“…The high ratio of water to solid, relatively low pH, and continuous agitation in the extraction process created a favorable environment for both soil Pb and apatite P release into the extraction solution. Reported data (9,(20)(21)(22)30) illustrate that the precipitation of pyromorphite is rapid when both Pb and P are in the solution. Thus, pyromorphite formation during extraction offers a plausible explanation for the differences observed by the two measurements and raises concern about the use of extractions to determine if amendments have altered the species of Pb present in the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRMRL research program's initial goal was to demonstrate the feasibility of altering the mineralogy of lead in soil in a laboratory setting by using thermodynamic and kinetic studies. Orthophosphate (aqueous phosphorus, hydroxyapatite, or phosphate rock) rapidly and effectively precipitates lead from solution to form a series of lead phosphates of low aqueous solubilities (27,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The final product of lead immobilization is primarily pyromorphite [Pb 5 (PO 4 ) 3 X, where X is OH, Cl, or F], which is stable under normal soil environmental conditions.…”
Section: Reducing Exposurementioning
confidence: 99%
“…For this reason, the rate of formation of pyromorphite from phosphate materials such as hydroxyapatite can be limited by the dissolution rates of the lead contaminants. Under neutral pH conditions, the observed solubility of lead and phosphate remain low, causing a major limitation for an efficient lead/phosphate reaction (Zhang and Ryan 1998). Dissolution of the initial lead phase has been reported to be the limiting factor in the formation of hydroxypyromorphite (Pb 5 (PO 4 ) 3 OH) at pH values between 5 and 8 (Laperche et al 1996).…”
Section: Apatite and Pyromorphite Chemistrymentioning
confidence: 99%